Analisis Kerusakan dan Perbaikan Jalan Beraspal pada Lapisan Asphalt Concrete-Wearing Course (AC-WC) di Kota Surabaya - Rindi Sekar Andika; Ari Widayanti (Proceedings Series on Physical & Formal Sciences, 2021)
AC-WC asphalt layer is a surface layer of flexible pavement construction that bears a direct load from the vehicle wheels. The increase in the number and load of traffic that occurs every year impacts road conditions and can cause damage. This requires analysis, repair and maintenance of roads for roads to function properly. The purpose of this study was to analyze road damage and provide alternative treatments for each road based on the type and level of damage that occurs. The method used was literature study, observation, documentation, and analysis with the PCI method. Observations were made on roads with class III flexible pavement in South Surabaya City. The results obtained were that the most dominant type of damage was crack damage, the level of road damage varies (low, medium, high severity) and there were different types of damage at the same point. The highest percentage and value of the damage were on Kembang Kuning Road and Pakis Tirtosari III Road. Based on the PCI method, the condition value of Dukuh Kupang XX Road was the lowest, at 25 (very poor). On Kembang Kuning Road and Pakis Tirtosari III Road maintenance work was needed, while Dukuh Kupang Road required road repairs.